The maternal condition as a limiting factor to prison: The eternal puerperal state exerted on female bodies - Contini , Alaerte Antonio Martelli; Fernandes , Juliana dos Santos Magalhães (Seven Editora, 2023)
This article addresses the context experienced by mothers in custody in Brazil, as well as the perceptions that the criminal justice system has about these women in particular and how this impacts the exercise of motherhood inside and outside prison institutions. Based on a Foucauldian analysis of disciplinary power and control mechanisms, a correlation was established between these elements and the puerperium. The methodology used was a literature review with an approach based on the theoretical basis of Michel Foucault. DOI:https://doi.org/10.56238/colleinternhealthscienv1-138